2015
DOI: 10.3389/fnsys.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of theta: natural manipulations of cognitive performance during hippocampal theta-contingent eyeblink conditioning

Abstract: Neurobiological oscillations are regarded as essential to normal information processing, including coordination and timing of cells and assemblies within structures as well as in long feedback loops of distributed neural systems. The hippocampal theta rhythm is a 3–12 Hz oscillatory potential observed during cognitive processes ranging from spatial navigation to associative learning. The lower range, 3–7 Hz, can occur during immobility and depends upon the integrity of cholinergic forebrain systems. Several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 294 publications
(409 reference statements)
1
14
0
Order By: Relevance
“…Further experiments are needed to specifically address this issue. Together, these correlational evidences support the hypothesis that D-serine released by astrocytes modulates specifically basal theta synchronization, that may entrain unit or ensemble firing in anatomically connected cortical areas (Anderson et al, 2009;Benchenane et al, 2010;Hoffmann et al, 1957 et al, 2003). Nevertheless, due to the lack of literature and causal observations that support this hypothesis, further work is needed to address these open questions: (1) Does astrocyte signaling modulate simultaneously several ensembles of the septal-entorhinal-hippocampal circuit, i.e., is there a spatial modulation of the theta generation or its phase?…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Further experiments are needed to specifically address this issue. Together, these correlational evidences support the hypothesis that D-serine released by astrocytes modulates specifically basal theta synchronization, that may entrain unit or ensemble firing in anatomically connected cortical areas (Anderson et al, 2009;Benchenane et al, 2010;Hoffmann et al, 1957 et al, 2003). Nevertheless, due to the lack of literature and causal observations that support this hypothesis, further work is needed to address these open questions: (1) Does astrocyte signaling modulate simultaneously several ensembles of the septal-entorhinal-hippocampal circuit, i.e., is there a spatial modulation of the theta generation or its phase?…”
Section: Discussionsupporting
confidence: 66%
“…The expression of transgenes occurred throughout the brain, displaying a typical mosaic-like distribution (Figure 1d-i) (Florian, Vecsey, Halassa, Haydon, & Abel, 2011;Sultan et al, 2015). We consistently verified the astrocyte specificity of transgene expression, by performing immunofluorescence staining of brain slices containing the hippocampus and prefrontal cortex (regions of critical interest for this study (Gordon, 2011;Hoffmann, Cicchese, & Berry, 2015;Lima et al, 2014;Oliveira et al, 2013;O'Neill et al, 2013)), using specific antibodies to target GFP and astrocytic or neuronal markers. GFP-labeling revealed only structures with the characteristic bushy astrocytic morphology (Florian et al, 2011;Khakh & Sofroniew, 2015;Pascual et al, 2005).…”
Section: R E Su Ltsmentioning
confidence: 77%
See 1 more Smart Citation
“…Theta oscillations are also important in acquisition and retention of hippocampal‐dependent tasks (Hoffmann, Cicchese, & Berry, ; Takehara‐Nishiuchi et al, ). In fact, Berry et al reported that presenting trials when theta power is high results in faster learning of trace (or delay) EBC as compared with presenting trials when theta is not present (Cicchese, Darling, & Berry, ; Seager, Johnson, Chabot, Asaka, & Berry, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while the process of pattern separation has been studied primarily within subregions of the hippocampal formation, it was recently reported that the cerebellum is also actively engaged during pattern separation tasks (Paleja et al, 2014 ). Conversely, tasks known to be heavily cerebellum-dependent can be significantly influenced by the hippocampus (Hoffmann and Berry, 2009 ; Wikgren et al, 2010 ; Hoffmann et al, 2015 ). A recognition of cerebellar-hippocampal interactions represents a paradigm shift as it challenges us to re-examine traditional notions of spatial and temporal processing and to better appreciate the collaborative efforts involved.…”
Section: Introductionmentioning
confidence: 99%